Concentrations of selected heavy metals and physicochemical properties in Forcados River in Sagbama Local Government Area of Bayelsa State, Nigeria - Ogbemudia, Egbere Moses; Nwoke, Emma Bright; Onisogenime, Awari Johnson (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
The concentration of selected heavy metals in water collected from eight different locations from the Forcados River in Sagbama Local Government Area of Bayelsa State, Nigeria was determined using AAS and the physicochemical properties were analysed using standard methods. The concentrations of heavy metals obtained in the water samples were in the order Ni> Cr> Zn> Cu> Pb> Cd. The concentrations(mg/l) of physicochemical properties in the water samples ranged from 5.76 to 6.76 for pH, 15.22 to 16.55 for NO3-, 146.23 to 206.39 for SO34, 715.62 to 817.66 for EC, 2.31 to 2.31 to 4.20 for TDS and 197.21 to 198. 50 for TOC. The concentrations(mg/l) of heavy metals in the water samples ranged from 2.25 to 4.76 for Pb, 5.77 to 6.90 for Cr, 1.03 to 2.17 for Cd, 2.25 to 3.87 for Cu, 4.09 to 6.15 for Zn and 6.08 to 7.99 for Ni. These results were within or lower than the permissible limits except pH, sulphates, and electrical conductivity. The result recorded for heavy metals were all higher than the permissible limits of WHO and NESREA. The result also indicated that the river water was contaminated/ polluted with heavy metals in the following order Cr >Pb > Ni>Cd. The study indicated that the heavy metals studied do not pose an environmental risk considering their low concentrations. It is recommended among others that all the activities contributing to the increased pollution of the river in the area be brought under control, to keep the environment safe for water organisms and people living in the area who depend on it for their livelihood.